2012
DOI: 10.1111/efp.12006
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of Chrysoporthe austroafricana in southern Africa determined using Vegetative Compatibility Groups (VCGs)

Abstract: Chrysoporthe austroafricana is one of the most damaging pathogens of Eucalyptus trees in southern Africa. It also occurs on non-native Tibouchina granulosa trees and native Syzygium species. Additional isolates of the pathogen from previously unstudied countries in the region have become available from survey studies. The aim of this study was to use VCGs to consider the diversity in populations of isolates collected in various countries in southern Africa (Malawi, Mozambique, Namibia, South Africa and Zambia)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Previous research has shown that various species in the Cryphonectriaceae undergo host shifts (Slippers et al ., ; Wingfield et al ., ) enabling them to infect tree species other than their native host species (Wingfield, ; Heath et al ., ; Gryzenhout et al ., ; Vermeulen et al ., , ). In this study, the pathogen C. sinomyrti collected from native R. tomentosa trees in GuangXi Province was widely distributed in areas close to the Eucalyptus plantations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that various species in the Cryphonectriaceae undergo host shifts (Slippers et al ., ; Wingfield et al ., ) enabling them to infect tree species other than their native host species (Wingfield, ; Heath et al ., ; Gryzenhout et al ., ; Vermeulen et al ., , ). In this study, the pathogen C. sinomyrti collected from native R. tomentosa trees in GuangXi Province was widely distributed in areas close to the Eucalyptus plantations.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculation tests on a clone of Eucalyptus showed that C. sinomyrti can infect and produce cankers on this host. Similar to species of Chrysoporthe , which has originated from native trees in the Myrtales and that infects non‐native plantation‐grown Eucalyptus (Heath et al ., ; Gryzenhout et al ., ; Vermeulen et al ., , ), C. sinomyrti from native R. tomentosa could, in the future, emerge as a pathogen of Eucalyptus trees in South China.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on Chrysoporthe species have focused on their taxonomy ( Gryzenhout et al 2004 ), population genetics ( Nakabonge et al 2007 , van der Merwe et al . 2010 , Vermeulen et al 2013 ), and geographical distribution ( Myburg et al . 2002 , Rodas et al .…”
mentioning
confidence: 99%
“…It is important to study the genetic diversity levels of exotic tree pathogen populations because more genetically diverse pathogens are more likely to overcome resistance [121][122][123]. Resistance (or tolerance) can be present in some tree individuals despite lack of co-evolution with the pathogen (as for European ash, F. excelsior, against ash dieback [64,113]) or can be obtained after long screening and breeding programmes [124][125][126].…”
Section: Example Of Application Referencementioning
confidence: 99%